The Effect of U-Dictionary Application Towards Students’ Pronunciation Mastery at Eleventh Grade of SMAN 3 Pandeglang in Academic Year 2021/2022 - Agustiani, Dea; Gumelar, Rizdki Elang; Munawaroh, Tatu (Journal of English Education Studies, 2022)
The research employs the quantitative research approach and quasi experimental method with pre-test and post-test design. It used a triangulation of data collection methods involving pre-test, treatment and post-test. The data obtained from two classes they are experiment and control class. The experimental class for this research was XI IPA 8 and the control class was XI IPA 3. Each class has 30 students, for a total sample is 60 students. The experimental class’s mean score on the pre-test was 51.33, while the control class’s mean score on the pre-test was 44.00. On the other hand, the mean score of experimental class post-test was 67.20, while the mean score of control class post-test was 59.20. Hypothesis calculating was done by using SPSS 22. The result obtained from hypothesis test is 0.00 < 0.05 it means that there is significant effect of using U-Dictionary application to students’ pronunciation mastery at the eleventh grade of SMAN 3 Pandeglang.